All the invisible things - Collins, Orlagh (Bloomsbury YA, London, 2019)
With Pez, the days felt endless - cycling, climbing trees, sucking sour sweets till our tongues burned. I'd give anything to be that girl again. For four years Vetty Lake has been keeping her heart in hiding. Since her mum died and her family moved out of London it's felt so much safer not to tell people how she really feels. She's never even told anyone she's attracted to girls as well as boys. But now Vetty's seventeen and coming back to London she's determined to start living out loud. She's convinced that reconnecting with her childhood best friend Pez is the key. She was always fearless around him. But when she sees Pez again, he's different. Guarded. It's like their special connection never existed. And suddenly Vetty's sure he's been hiding too.
Keywords: Bisexual people; Fiction; Young adult fiction